Modulating carbohydrate–protein interactions through glycoengineering of monoclonal antibodies to impact cancer physiology. (October 2016) - Chiang, Austin WT; Li, Shangzhong; Spahn, Philipp N; Richelle, Anne; Kuo, Chih-Chung; Samoudi, Mojtaba; Lewis, Nathan E
Graphical abstract: Highlights: Glycan–protein interactions modulate tumor cell killing. Different glycans can significantly alter the glycan–protein interactions. Glycan structure and location on mAb are essential properties need careful control. Glycoengineering can modify glycans on therapeutic mAbs with desired glycoforms. Systems biology can advance mAb glycoengineering toward a rational design era. Abstract : Diverse glycans on proteins impact cell and organism physiology, along with drug activity. Since many protein-based biotherapeutics are glycosylated and these glycans have biological activity, there is a desire to engineer glycosylation for recombinant protein-based biotherapeutics. Engineered glycosylation can impact the recombinant protein efficacy and also influence many cell pathways by first changing glycan–protein interactions and consequently modulating disease physiologies. However, its complexity is enormous. Recent advances in glycoengineering now make it easier to modulate protein-glycan interactions. Here, we discuss how engineered glycans contribute to therapeutic monoclonal antibodies (mAbs) in the treatment of cancers, how these glycoengineered therapeutic mAbs affect the transformed phenotypes and downstream cell pathways. Furthermore, we suggest how systems biology can help in the next generation mAb glycoengineering process by aiding in data analysis and guiding engineering efforts to tailor mAb glycan and ultimately drug efficacy, safety and affordability.